The defocusing mechanism of isochronous resonances - de Carvalho, R. E.; Favaro, G. M. (Elsevier B.V., 2005)
We present a numerical study concerning the defocusing mechanism of isochronous resonance island chains in the presence of two permanent robust tori. The process is initialized and concluded through bifurcations of fixed points located on the robust tori. Our approach is based on a Hamiltonian system derived from the resonant normal form. Choosing a convenient parameter in this system, we are able to depict a comprehensive analysis of the dynamics of the problem. (c) 2004 Elsevier B.V. All rights reserved.
Keywords: isochronous resonances; bifurcation; robust tori; stability distributions